Art journals in Morocco: new ways of seeing and saying. Issue 2 (14th March 2016) - Vogl, Mary
ABSTRACT: In the last half century, Moroccan artists, historians, critics and creative writers have undertaken the task of decolonising the history and criticism of their art. From the nineteenth century through independence in 1956, the story of Moroccan art was written largely from a colonialist perspective. In the 1960s and 1970s, this story was rewritten in broadly focused cultural journals such as Souffles, Intégral and Lamalif . In the subsequent decades, lesser known journals continued to reflect on the place of art and artists in Moroccan society. After the millennium, a specialised art press emerged. Current art magazines such as diptyk, launched in 2009, devote visual and verbal space to artists and critics. While a variety of media outlets, including newspaper journalism and television programming, have kept visual arts in the public eye, this essay focuses on the impact of cultural journals and magazines on the development of distinctly Moroccan ways of seeing and saying in the twenty-first century.